Antiglycative effect of fruit and vegetable seed extracts: inhibition of AGE formation and carbonyl‐trapping abilities. (3rd January 2013) - Mesías, Marta; Navarro, Marta; Gökmen, Vural; Morales, Francisco J
Abstract BACKGROUND Advanced glycation end‐products (AGEs) are the final products derived from the non‐enzymatic glycation process. AGEs are involved in the development of several health complications associated with diabetes and aging. Searching for anti‐ AGE extracts is necessary to mitigate the effects of age‐related pathologies. RESULTS The antioxidant and antiglycative activities of eight aqueous extracts of fruit and vegetable seeds were evaluated. All seed extracts (3.6 mg mL−1) exhibited anti‐AGE activity in protein–glucose assay, ranging from 20 to 92% inhibition compared with aminoguanidine (4.87 mmol L−1). Green pepper extract exerted the highest anti‐AGE activity. However, peach and pomegranate extracts exhibited the highest anti‐AGE activity in protein–methylglyoxal assay, ranging from 0 to 79% inhibition. Hazelnut, almond and sesame extracts were not effective when methylglyoxal was the promoter. Apricot and peach extracts appeared to inhibit the formation of AGEs through their capacity for direct trapping of 1, 2‐dicarbonyls (IC50=0.14 mg mL−1). No relationship between antioxidant and phenolic compound content and antiglycative activity was found. Therefore other hydrophilic constituents in addition to phenolic acids must be involved in the antiglycative activity of the extracts. CONCLUSION Aqueous extracts of fruits and vegetables can be considered in the prevention of glycation‐associated complications of age‐related pathologies. © 2012 Society of Chemical Industry